1987
DOI: 10.1007/bf00917241
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive vulnerability in children at risk for depression

Abstract: Cognitive, developmental, and psychodynamic theories all hypothesize that negative self-concepts acquired in childhood may induce vulnerability to depression. Children at risk because of maternal major affective disorder, compared with children of medically ill and normal mothers, were examined for evidence of negative cognitions about themselves, and were found to have more negative self-concept, less positive self-schemas, and more negative attributional style. It was further predicted that negative cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
117
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(128 citation statements)
references
References 23 publications
10
117
0
1
Order By: Relevance
“…Although several such models exist (e.g., Alloy, Lipman, & Abramson, 1992;Beck, 1976;Seligman, 1975), a common theme prevails in each: individuals whose thinking is characterized by self-blame, pessimism, and helplessness are at risk for the development of depression. In particular, attributional styles characterized by internal, stable, and global attributions for negative events have been linked to the development of depression in the presence of negative life events (Abramson, Seligman, & Teasdale, 1978;Alloy et al, 1992;Conley, Haines, Hilt, & Metalsky, 2001), and a growing literature indicates that cognitive vulnerability to depression may emerge early in life (Ingram, 2003;Jaenicke, Hammen, Zupan, Hiroto, Gordon, & Adrian, 1987).…”
mentioning
confidence: 99%
“…Although several such models exist (e.g., Alloy, Lipman, & Abramson, 1992;Beck, 1976;Seligman, 1975), a common theme prevails in each: individuals whose thinking is characterized by self-blame, pessimism, and helplessness are at risk for the development of depression. In particular, attributional styles characterized by internal, stable, and global attributions for negative events have been linked to the development of depression in the presence of negative life events (Abramson, Seligman, & Teasdale, 1978;Alloy et al, 1992;Conley, Haines, Hilt, & Metalsky, 2001), and a growing literature indicates that cognitive vulnerability to depression may emerge early in life (Ingram, 2003;Jaenicke, Hammen, Zupan, Hiroto, Gordon, & Adrian, 1987).…”
mentioning
confidence: 99%
“…As discussed earlier, children of parents with mental health issues have a much higher chance of experiencing mental health issues themselves than children of non-depressed parents (Coyne & Downey, 1991) and are also at higher risk for numerous other problems (Billings & Moos, 1983;Jaenicke et al, 1987;McCombs-Thomas & Forehand, 1993;Radke-Yarrow, 1998). Therefore, this suggests that more should be done to help alleviate depression and other mental health issues in recently separated parents as soon as possible.…”
Section: Mental Health Of Recently Separated Parentsmentioning
confidence: 98%
“…A negative impact on the child"s self-concept, less positive selfschemas, and a more negative attributional style has also been found to occur when parental mental health issues are present (Jaenicke et al, 1987). Therefore, research on the impact of separation is important as there are serious implications resulting for both children and adults.…”
Section: The Mental Health and Parenting Practices Of Recently Separamentioning
confidence: 99%
“…If the child received constant negative feedback from family, it is likely that the child forms negative self-perception, and this situation is becoming a risk factor for the child in terms of susceptibility to depression (39). It was found that children who are constantly criticized by his/her mother and receive negative feedback have a greater tendency to selfblame in the face of adverse events (40). Negative selfesteem has been shown to be associated positively with depression in numerous studies (41)(42)(43).…”
Section: Mediator Role Of Self-esteemmentioning
confidence: 99%